Readiness of Advance Care Planning Among Patients With Cardiovascular Disease - Fukue, Noriko; Naito, Emiko; Kimura, Masayasu; Ono, Kaoru; Sato, Shinichi; Takaki, Akira; Ikeda, Yasuhiro (Frontiers in Cardiovascular Medicine, 2022)
Background: Execution of advance care planning (ACP) in patients with heart failure is still inadequate. It is not easy for medical staff to provide the topic at the end of life. On the other hand, some patients wish to conduct ACP with medical staff. I investigated prognostic factors of the readiness of ACP among patients with cardiovascular diseases. Method: 81 patients (average age 81.8±10.3 years old, 42 men, 62 cases of heart failure) who introduced cardiac rehabilitation were asked about their experience and hope of ACP and understanding of their cardiovascular diseases in the questionnaire. Results: 9 patients (11.1%) experienced ACP and 28 (34.6%) were not performed but wished to execute ACP. Comparing patients who experienced or desired ACP (n=37) and those who did not (n=44), difference was not found in age, sex, heart failure, New York Heart Association classification, left ventricular ejection fraction, body mass index, Functional Independence Measure, dementia, cancer, chronic obstructive pulmonary disease, aspiration pneumonia, cerebrovascular disease, disease name understanding and cohabitation. Significant difference was observed in heart failure patients (odds ratio 5.56, p = 0.015) and Short Physical Performance Battery (odds ratio 1.25, p = 0.006). According to the prognosis evaluation scale, the EFFECT risk score and SPICT-JP, 31 patients (38.3%) were identified that had needs of ACP, of which 19 (61.3%) did not experience and hope of ACP. The hope of do not attempt resuscitation and life-prolonging treatment at the end-of-life reached about 70% among patients who requested ACP regardless of prognosis. Conclusions: Nearly half of patients introducing cardiac rehabilitation had experienced or desired ACP. And they tended to have heart failure and lower limb muscle strength. In the group of patients predicted to have a poor prognosis, there was no increase in experience or desire for ACP. It was suggested that patients who should be considered ACP were not carried out and not desired it.